Analysis of the Quality of the Formative Test Items for Physics Learning Using the Rasch Model in the 21st Century Learning - Muhammad Asriadi; Samsul Hadi (JIPF (Jurnal Ilmu Pendidikan Fisika), 2021)
Tests that have good quality are tests that have an even level of difficulty and can be completed as a whole by every respondent with every level of ability. This article aims to identify and analyze the quality of the items from the formative test material for static and dynamic fluids in physics subjects. This research used a survey with a cross-sectional method. Convenience sampling is a sampling technique used in this research. Then the sample in this study were 52 high school students class XI. The research instrument used a formative test for physics subjects, which were then analyzed using the Rasch model with the help of Winsteps software. The results of this study show that this formative test has a reliability level of 0.88 (very good) with a good level of problem difficulty and a good item fit level compatibility and there are no biased items in measurement so that this formative test is feasible to be used as a standard item in measuring students' abilities in materials of static and dynamic fluid in physics subjects.